Relationship between imatinib trough concentration and outcomes in the treatment of advanced gastrointestinal stromal tumours in a real-life setting. (April 2016) - Bouchet, Stéphane; Poulette, Sylvie; Titier, Karine; Moore, Nicholas; Lassalle, Régis; Abouelfath, Abdelilah; Italiano, Antoine; Chevreau, Christine; Bompas, Emmanuelle; Collard, Olivier; Duffaud, Florence; Rios, Maria; et al.
Abstract: Background: Imatinib has dramatically improved the prognosis of advanced gastrointestinal stromal tumours (GISTs). Clinical trial data showed that patients with trough imatinib plasma concentrations (Cmin) below 1100 ng/ml (quartile 1) had shorter time to progression, but no threshold has been defined. The main objective of this study was to investigate in advanced GIST whether a Cmin threshold value associated with a longer progression-free survival (PFS) could be specified. This would be the first step leading to therapeutic drug monitoring of imatinib in GIST. Patients and methods: Advanced GIST patients (n = 96) treated with imatinib 400 mg/d (41 stomach, 34 small bowel, and 21 other primary site localisations) were prospectively included in this real-life setting study. Routine plasma level testing imatinib (Cmin) and clinical data of were recorded prospectively. Results: Small bowel localisation was associated with an increased relative risk of progression of 3.09 versus stomach localisation (p = 0.0255). Mean Cmin (±standard deviation) was 868 (±536) ng/ml with 75% inter-individual and 26% intra-patient variability. A Cmin threshold of 760 ng/ml defined by log-rank test was associated with longer PFS for the whole population (p = 0.0256) and for both stomach (p = 0.043) and small bowel (p = 0.049) localisations when analysed separately. Multivariate Cox regression analysis found that Cmin above 760 ng/ml was associated with 65% reduction risk of progression (p = 0.0271) in the whole population independently of the anatomical localisation. Conclusion: Concentration of imatinib significantly influences duration of tumour control treatment in GIST patients with a Cmin threshold of 760 ng/ml associated with prolonged PFS in real-life setting. Highlights: Definition of an imatinib threshold is proposed in a real-life setting. An imatinib Cmin threshold of 760 ng/ml was associated with longer progression-free survival (PFS) in gastrointestinal stromal tumours (GISTs). Same threshold associated with longer PFS for both stomach and small bowel localisations. Imatinib therapeutic drug monitoring may be useful in real-life settings for GISTs treatment management.